Overview of the Functional Lactic Acid Bacteria in Fermented Milk Products - Barretto Penna, Ana Lúcia [UNESP]; de Paula, Aline Teodoro [UNESP]; Casarotti, Sabrina Neves [UNESP]; Silva, Luana Faria [UNESP]; Diamantino, Vivian Ribeiro [UNESP]; Todorov, Svetoslav Dimitrov (Taylor & Francis, 2014)
Lactic acid bacteria (LAB) are known through ages for their wide applications in food, pharmaceutical, and biotechnological industries. LAB are involved in numerous food fermentations, are accepted as generally recognized as safe (GRAS), and are associated with the probiotic properties of some commercial products. Moreover, the biotechnological production of compounds by LAB is considered to be of low environmental pollution. The LAB as competitive microbiota have a long history of application in fermented foods. Due to their metabolic properties, LAB are generally employed because of their positive contribution to the avor, texture, and nutritional value in food products, besides their natural antimicrobial properties that extend the product shelf life. The main functional role of LAB in milk fermentation is to biopreserve the product due to fermentation, and consequently, the production of acid results in an extended shelf life and enhanced safety; to produce organic acids, carbonyl compounds, and partial hydrolysis of the proteins and/or fats and improve the sensory quality of the product; to produce texturing compounds, such as exopolysaccharides (EPSs) that improve the rheological properties of fermented milk products (i.e., viscosity and texture); to produce antimicrobial compounds, such as bacteriocins, that may have potential uses as food preservatives; and to produce bioactive compounds, such as vitamins, antioxidants, fatty acids, or with the use of probiotic microorganisms that contribute to therapeutic properties to fermented milks.